Contributing factors towards enhancement of social cohesion in virtual communities - Sahharon, Hamizah (2021)
An ethnically heterogeneous population requires the acceptance of differing values and tolerance for diversity per se. Frequent changes within the environment lead to uncertainty in human society. Several social exchange theories have justified factors that influence social cohesion, but it was the theory of relational cohesion that illustrates the micro and macro level of human interactions. Given the rapid technological changes in society, people face changes in almost every area of the economy, society, and culture, thus maintaining social cohesion can be quite challenging because commitment requires emotional reactions. To influence a person’s membership attitude and behavior towards a group, the anxiety and uncertainty management theory said the members should be cooperative, trusting, tolerate diversity, and emit positive emotions. Youth nowadays prefer spending time on social networking sites as a virtual community platform to communicate effectively. To emit cooperative, trusting, and positive attributes in virtual communities, members can communicate effectively by having tolerance for diversity. Referring to the universal-diverse orientation model, multicultural awareness is developed when people are mindful and accept both the similarities and differences among people to avoid offending others. Hence, to attain the truth about this phenomenon lies in the deductive approach based on the theoretical research framework. This research is quantitative in nature and a multi-stage homogeneous sampling approach is applied, whereby 600 youths are chosen to represent each zone for inclusivity of the youth population and equal distribution. The data is analyzed using SPSS and Partial Least Square (PLS) Structural Equation Modelling (SEM) to explore the theoretical framework. In conclusion, interaction within social networking sites or virtual communities can enhance the sense of social cohesion among Malaysian youths if they socially categorized themselves as being part of the group, feel connected to others, personally and socially identify themselves as members, and positively react to others. Rural youths especially, have better communication effectiveness in virtual communities than their urban counterparts when they manage their level of anxiety and uncertainty through personal/social identity, motivation to interact, and situational processes. Although communication effectiveness and tolerance of diversity did not affect anxiety and uncertainty management directly in enhancing the sense of social cohesion in virtual communities, it was proven that a micro-macro level online interaction could enhance social cohesion among youth.